The Impact of Clean Water Pollution from Nickel Mining Activities in Kabaena, Southeast Sulawesi - Ramadhan Tosepu; Dhea Resky Apriana; Liberthy Mendila Tappo; Indri Reva Wardani (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Water is an essential element for the survival of all living organisms. Human activities are closely intertwined with the availability and quality of water. However, environmental degradation resulting from waste generated by mining, energy, and mineral extraction activities poses significant threats to water quality, particularly in river systems. One such affected area is Kabaena Island, where mining operations have contributed to the deterioration of river and marine water quality. Objective: This study aims to examine the impact of mining waste pollution on the health, livelihood, and environment of communities on Kabaena Island. Methods: This research employed a qualitative descriptive design, utilizing online research methods (ORM) to collect and analyze secondary data in the form of text and images. Results: Data obtained from community reports indicate that 71% of residents have experienced health problems associated with mining waste exposure. Furthermore, 83% of the population reported a decline in income, and 94% perceived significant environmental degradation linked to nickel mining activities. Conclusion: Water pollution on Kabaena Island, Southeast Sulawesi, is primarily attributed to waste generated by nickel mining operations, which contaminates both river and marine ecosystems. The presence of heavy metals exceeding safety thresholds poses serious risks to ecological integrity, public health, and the socio-economic well-being of local communities. Keywords: Nickel, Heavy Metals, Mining, Public Health, Indonesia